Reexamining feedback in the context of different rhetorical patterns of writing - AL Harrasi, Kothar Talib Sulaiman (Language Testing in Asia, 2023)
Drawing upon research on the ways texts work as communication across different disciplines, this study investigated teacher and student feedback practices on three different patterns of writing: comparison-contrast essays, opinion essays, and cause-and-effect essays. The data were collected through three qualitative techniques: interviews, class observations, and an analysis of course documents and student-marked writing. The results showed that the participants did not always adhere to rhetorical features of different writing patterns when giving and responding to feedback. Rather, practices of feedback were majorly shaped by their beliefs about academic writing, assessment, and cognitive issues with rhetorical patterns. The results suggest a need for raising student and teacher awareness of the values of different patterns of writing for subject-domain studies; building a constructive alignment between writing course objectives, course assessment, and feedback practices; and involving students in the academic acculturation process.